Molecular modification proposal: analysis of physicochemical, pharmacokinetic and toxicological parameters "in silico" of barbituric drugs - Silva, Henrique Hidelbrando Mendes; Alves, Matheus Henrique Pereira; Gonçalves, Renan José Sousa; Pereira, Nathalia de Aguiar; Affonso, Cristiano Ribeiro Goncalves (Seven Editora, 2023)
This research aimed to propose molecular modifications and compare the characteristics of three barbiturate drugs and their analogues developed in silico through procedures and computational techniques using free programs. Barbiturates were the class chosen for this study, the selected drugs were: Phenobarbital, Pentobarbital and Amobarbital, being modified through simulations in silico. Three analogues were proposed, being analyzed and compared with the prototypes, using the free programs, Marvinsketch, where it was possible to evaluate parameters such as: Log P, hydrogen donors/acceptors and Van Der Walls Surface. In PreADMET, parameters such as BHE, HIA, Caco-2, MDCK, CYP-3A4, Ames Test, Carcinogenicity (Rats) and hERG Risk were obtained. Through the Osiris Property Explorer, the following parameters were evaluated: Mutagenicity, tumorigenicity, irritability, reproductive effect, solubility, molecular weight, polarity, druglikeness and Drug-Score. With the results obtained in PreADMET referring to BHE, the analogues BBT-F and BBT-A obtained better results, while the BBT-P had a worsening in the result. In relation to HIA, the values proved to be satisfactory, exhibiting good intestinal absorption. As for toxicity, the Ames test was verified, where all molecules were mutagenic. With the results obtained in Osiris, all the prototype drugs proved to be mutagenic, while in the analogues, only BBT-P showed mutagenicity. As for tumorigenicity, the prototype drugs remained at medium to high risk, while analogue drugs all showed non-tumorigenic results. Therefore, it is concluded that it was possible to make a preliminary, fast and low-cost analysis, helping in the research of new drugs through computational tools.DOI:https://doi.org/10.56238/alookdevelopv1-039